The Use of Forensic DNA Phenotyping in Predicting Appearance and Biogeographic Ancestry - M. Schneider, Peter (Dtsch Arztebl Int, 2019)
BACKGROUND: Persons whose identifying DNA profile (STR profile) is not yet known to the ingvestigating authorities cannot be identified by standard forensic DNA analysis (STR profiling) as it is now practiced. In view of the current public debate, particularly in Germany, on the legalization of so-called forensic DNA phenotyping, we present its scientific basis, societal aspects, and forensic applications and describe the analytic techniques that are now available. METHODS: This review is based on pertinent publications that were retrieved by a selective search in PubMed and in public media, and on the authors’ own research. RESULTS: Forensically validated DNA test systems are available for the categorization of eye, hair, and skin color and the inference of continental biogeographic ancestry. As for statistical measures of test accuracy, the AUC (area under the curve) values lie in the range 0.74–0.99 for eye color, 0.64–0.94 for hair color, and 0.72–0.99 for skin color, depending on the predictive model and color category used.The corresponding positive predictive values (PPV) are lower. Empirical social-scientific research on forensic DNA phenotyping has shown that preserving privacy and protecting against discrimination are major ethical and regulatory considerations. CONCLUSION: All three methods of forensic DNA phenotyping—the predition of externally visible characteristics, biogeographic ancestry, and the estimation of age from crime scene DNA—require a proper regulatory framework and should be used in conjunction with each other. Before forensic DNA phenotyping can be implemented in forensic practice, steps must be taken to minimize the risks of violation of privacy and of ethnic discrimination and to ensure that these methods are used transparently and proportionately.